Teknik Mekanika Tubuh Mengurangi Tingkat Nyeri Punggung Bawah pada Ibu Hamil Trimester III: Body Mechanics Techniques to Reduce Lower Back Pain among Third Trimester of Pregnant Women - Nur Azizah Putri Rahayu; Rafika Rafika; Lili Suryani; Hadriani Hadriani (Jurnal Bidan Cerdas, 2020)
In order to reduce and prevent back pain complaints and to form safe and comfortable daily activities during pregnancy, pregnant women need proper body mechanics. The purpose of this research is to know the influence of the application of mechanical body mechanics with lower back pain of the III trimester of pregnant women. This type of research is pre-experimental with one group Pretest posttest design. This research was conducted in the working area of Puskesmas Sangurara. The population in this study is all III-trimester pregnant mothers with a sample number of 31 people, taken with a consecutive sampling technique. The treatment given is the technique of body mechanics observed during 1 week. Data collection using an observation sheet. The results showed before performing mechanical body mechanics there were 71% of respondents experienced moderate pain and after conducting mechanical body mechanics there were 74.2% of respondents experienced mild pain. Based on the Wilcoxon test obtained a p-value <0.001, with an average decrease in pain, is 7.50. The conclusion is the application of body mechanics techniques significantly affect the lower back pain of the III trimester of pregnant women.